Fauna and Station Distribution of Coccinellids (Coleoptera: Coccinellidae) in the Right-Bank Forest Steppe - Medvid, Y. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2017)
Presented research results of station Coccinellids distribution in the conditions of the Right-Bank Forest-Steppe, on spiked cereals, perennial leguminose grasses, beets, sunflowers, corns, grasslands and parklands. Educed 19 species of Coccinellids from 14 genera from 4 subfamilies. Investigated quantity fluctuations of ladybirds during a season and there placing on different stations.